IMPACT OF NATIONAL HUMAN CAPITAL ON POPULATION MIGRATION ACTIVITY - KUZMINSKA, Natalia; KOZHEMIACHENKO, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article evaluates the national human capital as a factor in the migration activity of the population. For the study, data were taken from open international and national databases Ukraine, Republic of Moldova, the Russian Federation, Republic of Belarus, Republic of Poland. The assessment of the value of human capital was carried out using the indicators-based approach. All data were divided into four groups. Two groups characterize the costs of human capital formation (intelligence, knowledge and health). The other two groups characterize the conditions for obtaining income from human capital (implementation of high-quality economic production; quality of life). Based on the collected data, a cluster analysis was carried out. As a result of the study, it was concluded that the factors that characterize the conditions for receiving income from human capital have the greatest influence on migration. The research was carried out until February 24, 2022. Therefore, they can become the basis for studying the migration activity of the population in the new military-economic and political realities.